2022
DOI: 10.3390/ijms24010148
|View full text |Cite
|
Sign up to set email alerts
|

The Greatwall–Endosulfine Switch Accelerates Autophagic Flux during the Cell Divisions Leading to G1 Arrest and Entry into Quiescence in Fission Yeast

Abstract: Entry into quiescence in the fission yeast Schizosaccharomyces pombe is induced by nitrogen starvation. In the absence of nitrogen, proliferating fission yeast cells divide twice without cell growth and undergo cell cycle arrest in G1 before becoming G0 quiescent cells. Under these conditions, autophagy is induced to produce enough nitrogen for the two successive cell divisions that take place before the G1 arrest. In parallel to the induction of autophagy, the Greatwall–Endosulfine switch is activated upon ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Previous results from our lab have shown that igo1Δ phenotypes could be restored by decreasing PP2A/B55 activity 31 , including the reduction in viability during quiescence (Supplementary Fig. 2a).…”
Section: Telomeric Detachment Is Mediated By Reduced Levels Of the Ra...mentioning
confidence: 63%
“…Previous results from our lab have shown that igo1Δ phenotypes could be restored by decreasing PP2A/B55 activity 31 , including the reduction in viability during quiescence (Supplementary Fig. 2a).…”
Section: Telomeric Detachment Is Mediated By Reduced Levels Of the Ra...mentioning
confidence: 63%